The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1756-0500-7-891
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of time in therapeutic range in anticoagulated patients: a single-center, retrospective, observational study

Abstract: BackgroundThe percentage of time during which the patients have the INR within the target values (i.e. Time in Therapeutic Range [TTR]) is a measure of anticoagulation quality with Vitamin K Antagonists (VKA). To evaluate the quality of anticoagulation using TTR according to the Rosendaal method, we performed an observational, retrospective study. We included all outpatients who attended the cardiology anticoagulation clinic of a Portuguese hospital (2011–2013), whose target INR was 2.0-3.0.Results377 VKA-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 20 publications
2
40
1
3
Order By: Relevance
“…This is in line with prior studies of DOACs, which have been routinely found to have less CNS bleeding . The majority of the patients in the traditional anticoagulation group were receiving VKAs, which are prone to significant time outside of the therapeutic range . It is possible that supratherapeutic values in patient with cirrhosis are more dangerous than in patients without hepatic impairment, and while DOAC metabolism in cirrhosis may lead to higher mean therapeutic levels with certain DOACs, it is likely consistent, with less extreme peaks and troughs.…”
Section: Discussionsupporting
confidence: 81%
“…This is in line with prior studies of DOACs, which have been routinely found to have less CNS bleeding . The majority of the patients in the traditional anticoagulation group were receiving VKAs, which are prone to significant time outside of the therapeutic range . It is possible that supratherapeutic values in patient with cirrhosis are more dangerous than in patients without hepatic impairment, and while DOAC metabolism in cirrhosis may lead to higher mean therapeutic levels with certain DOACs, it is likely consistent, with less extreme peaks and troughs.…”
Section: Discussionsupporting
confidence: 81%
“…9 But Daniel Caldeira et al reported 44.3% of their patients who had a mean TTR < 60%, were at an increased risk of thrombotic and hemorrhagic events. 10 Even the larger randomized trials of newer oral anticoagulants and warfarin in Atrial fibrillation, provided further data about worldwide difficulty in maintaining the TTR level. The mean TTR values of the major large randomized trials (ROCKET-AF trial, ARISTOTLE trial and the RELY trial) were 55.2%, 62.2% and 64%.…”
Section: Discussionmentioning
confidence: 99%
“…Se calculó el TRT mediante el método de Rosendaal (18,19,20), considerándose como control óptimo TRT ≥60% y control subóptimo TRT <60%. Este es el valor utilizado en los estudios clínicos internacionales (19,20).…”
Section: Procedimiento Y Técnicasunclassified
“…Se calculó el TRT mediante el método de Rosendaal (18,19,20), considerándose como control óptimo TRT ≥60% y control subóptimo TRT <60%. Este es el valor utilizado en los estudios clínicos internacionales (19,20). Los grupos fueron sometidos a análisis para determinar la asociación con los factores edad, género, grado de instrucción, dependencia funcional, deterioro cognitivo, comorbilidades, discontinuidad terapéutica y polifarmacia, así como el porcentaje de ACV y sangrado en ambos grupos.…”
Section: Procedimiento Y Técnicasunclassified